Dental status in the Polish senior population and its correlates—Results of the national survey PolSenior. (27th July 2018) - Mehr, Katarzyna; Olszanecka‐Glinianowicz, Magdalena; Chudek, Jerzy; Szybalska, Aleksandra; Mossakowska, Małgorzata; Zejda, Jan; Wieczorowska‐Tobis, Katarzyna; Grodzicki, Tomasz; Piotrowski, Paweł
Abstract : Objective: The aim of the study was to assess dental status of Polish seniors having and wearing dentures in relation to demographic, socioeconomic and lifestyle factors. Background: Tooth loss is associated with deterioration of general health status. The epidemiological data on dental status in Poland, including Polish seniors, are fragmented. Materials and methods: The study cohort consisted of 4524 randomly selected participants, aged 65 years and over, representative for Polish seniors. Demographic, socioeconomic, lifestyle factors and dental status were collected using standardised questionnaires. Results: The prevalence of partial and complete edentulism in the Polish senior population was estimated at 45.7% and 47.1%, respectively. Fourteen point four per cent (14.4%) of complete edentulous participants and 31.1% with partial edentulism (1‐19 natural teeth) did not have dentures, and one‐twelfth of respondents having dentures were not wearing them. The independent correlates of complete edentulism were: female sex, advanced age, rural dwelling, lower education level, physical work in the past, smoking and diabetes. Male sex, age 90+, rural dwelling, type of work, dependence in activities of daily living and partial edentulism were independent correlates of not having dentures and denture disuse. Lower than average personal income was only significant for not having dentures. Conclusions: Complete edentulism is frequent among older Poles and affects almost 50% of them. It is associated with female sex, age, rural dwelling, poor economic status, smoking and diabetes. Rural dwelling and dependence of daily living are significant correlates of not having dentures and denture disuse.